Analysis of International Standard IEC/TS 62580-2 for On-board Video Surveillance System - LIU Gui; ZHOU Guifa; XIE Zhe; WANG Qiuhua (机车电传动)
Based on the background, preparation and contents of the video surveillance international standard, the on-board video surveillance system in both system level and functional level with the system breakdown structure (SBS) and functional breakdown structure (FBS) was analyzed, and the related functions of on-board video surveillance system were introduced. Based above, the idea was proposed to establish the national standard or industry standard in the field of on-board video surveillance system.